Postoperative Atypical Hemolytic Uremic Syndrome Associated with Complement C3 Mutation - Matsukuma, Eiji (Case Rep Nephrol, 2014)
Atypical hemolytic uremic syndrome (aHUS) can be distinguished from typical or Shiga-like toxin-induced HUS. The clinical outcome is unfavorable; up to 50% of affected patients progress to end-stage renal failure and 25% die during the acute phase. Multiple conditions have been associated with aHUS, including infections, drugs, autoimmune conditions, transplantation, pregnancy, and metabolic conditions. aHUS in the nontransplant postsurgical period, however, is rare. An 8-month-old boy underwent surgical repair of tetralogy of Fallot. Neurological disturbances, acute renal failure, thrombocytopenia, and microangiopathic hemolytic anemia developed 25 days later, and aHUS was diagnosed. Further evaluation revealed that his complement factor H (CFH) level was normal and that anti-FH antibodies were not detected in his plasma. Sequencing of his CFH, complement factor I, membrane cofactor protein, complement factor B, and thrombomodulin genes was normal. His ADAMTS-13 (a disintegrin-like and metalloprotease with thrombospondin-1 repeats 13) activity was also normal. However, he had a potentially causative mutation (R425C) in complement component C3. Restriction fragment length polymorphism analysis revealed that his father and aunt also had this mutation; however, they had no symptoms of aHUS. We herein report a case of aHUS that developed after cardiovascular surgery and was caused by a complement C3 mutation.